2020
DOI: 10.1038/s41467-020-15555-8
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine synthases CYSL-1 and CYSL-2 mediate C. elegans heritable adaptation to P. vranovensis infection

Abstract: Parental exposure to pathogens can prime offspring immunity in diverse organisms. The mechanisms by which this heritable priming occurs are largely unknown. Here we report that the soil bacteria Pseudomonas vranovensis is a natural pathogen of the nematode Caenorhabditis elegans and that parental exposure of animals to P. vranovensis promotes offspring resistance to infection. Furthermore, we demonstrate a multigenerational enhancement of progeny survival when three consecutive generations of animals are expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
96
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(106 citation statements)
references
References 42 publications
10
96
0
Order By: Relevance
“…Inherited immunity is a nascent and rapidly growing field of research, with important consequences for our understanding of health and evolution. Multiple studies have now demonstrated that parental exposure to one pathogen can protect offspring against subsequent exposure to the same pathogen 1,13,19,43 . Several studies have also shown that parents exposed to a particular stress can produce progeny that are protected against the same stress, and that abiotic stress can provide transgenerational resistance to pathogenic infection 5,6,[44][45][46] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inherited immunity is a nascent and rapidly growing field of research, with important consequences for our understanding of health and evolution. Multiple studies have now demonstrated that parental exposure to one pathogen can protect offspring against subsequent exposure to the same pathogen 1,13,19,43 . Several studies have also shown that parents exposed to a particular stress can produce progeny that are protected against the same stress, and that abiotic stress can provide transgenerational resistance to pathogenic infection 5,6,[44][45][46] .…”
Section: Discussionmentioning
confidence: 99%
“…We found that the offspring of N. parisii infected mutants still became protected against infection ( fig. S8, A to D) 19,36 . In addition, we found that the master immune regulator PMK-1 was not required for the induction of inherited immunity, consistent with this pathway not being involved in immunity to N. parisii ( fig.…”
Section: The Parental Transcriptional Response To Infection Triggers mentioning
confidence: 99%
“…In addition to inducing avoidance behavior and dauer formation in descendants, exposure to bacterial pathogens can induce heritable resistance to infection. Non-lethal adult exposure to the novel C. elegans pathogen Pseudomonas vranovensis induces resistance to the same pathogen in first-generation progeny, an intergenerational effect, with a substantial effect size ( Burton et al, 2020 ). Exposure for three consecutive generations triggers resistance for two subsequent generations, suggesting epigenetic inheritance but falling one generation short of the three-generation gold standard.…”
Section: Examplesmentioning
confidence: 99%
“…In addition to food-seeking related behavior, exposing the worms to pathogenic bacteria generates intergenerational effects on other physiological traits critical for survival. For example, exposure to Pseudomonas vranovensis, another bacterium pathogenic to C. elegans, generates multigenerational effects and enhances immune resistance to the pathogen in the offspring (Burton et al, 2019). Meanwhile, exposure to certain pathogenic bacteria for two consecutive generations induces formation of dauers, a dormant development stage that is highly resistant to environmental stresses (Palominos et al, 2017).…”
Section: Intergenerational Effectsmentioning
confidence: 99%